Knowledge and Perception of Caregivers Regarding Adverse Events Following Immunization and Associated Predictors at Hospitals in Osogbo, Southwestern Nigeria: A Cross‐Sectional Study - Funso Abidemi Olagunju; Samuel Olorunyomi Oninla; Sunday Charles Adeyemo; Abimbola Ololade Odeyemi; Kehinde Awodele; Efeturi Agelebe; Abisola Oluwatoyin Omoboyeje; Muritala Adewale Ibrahim; Ayodeji Oluwaseun Ogungbemi; Ayodele Raphael Ajayi; Eniola Dorcas Olabode; Oladunni Opeyemi; et al. (Health Science Reports, 2026)
ABSTRACT Background and Aims Adverse events following immunization (AEFI) can erode trust in vaccines and contribute to immunization dropout. Caregivers usually observe an AEFI first and decide whether it is reported and whether the child returns for later doses, yet their knowledge and perception are rarely assessed together. This study assessed caregivers' knowledge and perception of AEFI, and associated factors, in Osogbo, Southwestern Nigeria. Methods This hospital‐based cross‐sectional study included 368 caregivers presenting children for routine vaccination at three hospitals in Osogbo between October 15, 2025, and February 2, 2026, selected by proportionate systematic random sampling. A pretested, self‐administered questionnaire captured sociodemographic characteristics and 10 knowledge and 10 perception items; scores were graded poor (0–3), fair (4–6), or good (7–10). Associated factors were examined with Pearson's χ 2 test, independent predictors with multinomial logistic regression (good grade as reference), and correlation with Pearson's r . All tests were two‐sided; significance was set at p < 0.05 (SPSS version 27.0). Results Most caregivers had good knowledge (254; 69.0%) and good perception (220; 59.8%), but only 216 (58.7%) knew an AEFI may occur without a causal link to the vaccine. Age group and residential status were associated with knowledge; these, plus educational and occupational status and socioeconomic class, were associated with perception (all p < 0.05). Caregivers aged 25–34 years (AOR 0.30, 95% CI 0.089–0.998) and those living within Osogbo (AOR 0.44, 95% CI 0.225–0.84) had lower odds of fair versus good knowledge. Knowledge and perception scores were moderately correlated ( r = 0.442, p < 0.001). Conclusion Knowledge and perception of AEFI were largely good, yet many caregivers attribute every post‐vaccination event to the vaccine. Interventions targeting caregivers with lower education, lower socioeconomic status and peri‐urban residence, delivered through immunization clinics, community leaders and social media, may improve AEFI literacy and reduce vaccine hesitancy.